A (dis)pleasure of influence - Schwarz, David (Muzikološki zbornik, 2009)
In 'A (dis)pleasure of influence: George Rochberg's Caprice variations for unaccompanied violin (1973)' I bring together Harold Bloom's The anxiety of influence, several recent and particularly successful adaptations of Bloom to music, and offer a theory of musical (dis)pleasure informed by post-Lacanian psychoanalysis.
Keywords: Bloom, Harold: The anxiety of influence; glasba; hipotaksa; kolaž; music; parataksa; pentlje; Rochberg, George: Caprice variations for unaccompanied violin; vplivi